2018
DOI: 10.1016/j.actbio.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

3D bioprinted functional and contractile cardiac tissue constructs

Abstract: Bioengineering of a functional cardiac tissue composed of primary cardiomyocytes has great potential for myocardial regeneration and in vitro tissue modeling. However, its applications remain limited because the cardiac tissue is a highly organized structure with unique physiologic, biomechanical, and electrical properties. In this study, we undertook a proof-of-concept study to develop a contractile cardiac tissue with cellular organization, uniformity, and scalability by using three-dimensional (3D) bioprint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
194
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 248 publications
(194 citation statements)
references
References 47 publications
0
194
0
Order By: Relevance
“…Recent work from our group has shown that anchoring of cellular constructs is critical for the development of organized tissue structures in 3D bioprinted tissue (Wang, Lee, Cheng, Yoo, & Atala, 2018). Such anchor points are understood to enable the intrinsic force in the system to induce compaction phenomenon within the tissue construct (H. W. Kang et al, 2016;Smith, Passey, Greensmith, Mudera, & Lewis, 2012).…”
Section: Biomechanical Assessment Of In Vitro Modelmentioning
confidence: 99%
“…Recent work from our group has shown that anchoring of cellular constructs is critical for the development of organized tissue structures in 3D bioprinted tissue (Wang, Lee, Cheng, Yoo, & Atala, 2018). Such anchor points are understood to enable the intrinsic force in the system to induce compaction phenomenon within the tissue construct (H. W. Kang et al, 2016;Smith, Passey, Greensmith, Mudera, & Lewis, 2012).…”
Section: Biomechanical Assessment Of In Vitro Modelmentioning
confidence: 99%
“…Thus, this construct effectively demonstrates the unique capability of bioprinting to print the complex trabecular structures of a whole heart through CAD modeling while using remarkably low-viscosity bioinks that would otherwise not be printable [195]. Atala et al also developed a contractile cardiac tissue construct with cellular organization, uniformity, and scalability through a 3D bioprinting approach [196]. The bioprinted cardiac tissue constructs were fabricated by processing three key components: a primary cardiomyocyte laden fibrin-based hydrogel, a sacrificial hydrogel, and a supporting polycaprolactone (PCL) polymeric frame.…”
Section: Regeneration and Pharmacological Study Of 3d Bioprintedcardimentioning
confidence: 99%
“…The bioprinted cardiac tissue constructs were fabricated by processing three key components: a primary cardiomyocyte laden fibrin-based hydrogel, a sacrificial hydrogel, and a supporting polycaprolactone (PCL) polymeric frame. The cardiac constructs exhibited a spontaneous synchronous contraction in culture, and also displayed physiological responses to known cardiac drugs in terms of beating frequency and contraction forces [196]. A nano-reinforced hybrid cardiac patch laden with human coronary artery endothelial cells (HCAECs) was fabricated by UV-assisted 3D bioprinting to improved electrical, mechanical, and biological behaviors [197].…”
Section: Regeneration and Pharmacological Study Of 3d Bioprintedcardimentioning
confidence: 99%
“…It is achieved by the formation of gap junctions in cardiac muscles and smooth muscles, but not in skeletal muscles. Many researchers have successfully engineered hydrogel‐based cardiac muscle tissues using microfabrication technologies such as 3D bioprinting . And electromechanical coupling between CMs were observed.…”
Section: Cell–cell Interactionmentioning
confidence: 99%
“…Electronic readouts were obtained to reflect the contractile stresses. In another study, a 3D printed microspring device was used for the force measurement of cell‐laden cardiac patches . With the consistent stiffness in a wide range, the device could conveniently convert contracting motion to force.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%